The effectivenesss of field trip in the teaching of EOP to Business Management and ICT Students at IIUM: a case study - Yusof Khan , Zarinah Jan; Othman, Khairiah; Adam, Zalika (2009)
Malaysia is currently experiencing an emerging trend to focus on workplace specific language needs. This is to meet the present demands of social and economic development where employers are seeking young vibrant employees with high English language proficiency, coupled with strong interpersonal skills and confidence, as an essential condition to work in today's global context. In line with this, a survey conducted by the Federation of Mlaysian Manufacturers (FMM, 2007) among its members revealed that the top five difficulties in recruiting fresh graduates were: (1)lack of industrial training, (2)communication problems/ weak command in English, (3)weak problem solving skills, (4)job hopping and (%)lack of confidence. This paper investigates to see if the field trip activity, which is one of the components in the English for Specific Purposes (EOP) syllabus for the Business Management and ICT final students, can help graduates meet the requirements of the incumbent employment market. the objective of the study is show that it is imperative for all higher learning institutions to prepare students with sound communicative, interpersonal and problem solving skills before they go into the market place. The methodology used consists of pre and post survey questionnaires to investigate students ' preparation emotionally and physically before the field trip and their experience after the field trip. Findings from the research do not only indicate that students were more prepared and confident to face people in the workplace, but also made them realize the importance of mastering the English language to land a better job opportunity.